Las deformaciones de la verdad en política. Del discurso al sometimiento - Nicasio Álvarez, Israel (2017)
Hannah Arendt says that in politics it is important to achieve some goals that are convenient for a certain group, in order to get power. The only way to achieve these goals in the political environment is the use of ideology, that is, the creation of a speech that permits observed reality to have the tincture it needs in order to be positively assimilated. Lies in politics are connected with the capacity of action, because both are controlled by human imagination and action is the principal element of politics. The possibility of speech generation and the ideology control have an important characteristic: lies work because of the capacity of creating images